Spectroscopic, Diagnostics, and Surface Modification of Stainless Steel Doped with Ti Plasma Produced by DC Magnetron Sputtering and Used in Biomedical Applications - Mustafa A. Mahmood; Riyam Adnan Hammudi (Tribology in Industry)
Significant developments have been made in the plasma spray process in recent years. In this process, high-quality, denser coatings can be produced. In the current study, titanium films with ~3 nm thickness were developed on 304 stainless steel bars by DC magnetron sputtering technique. It was determined that the developed titanium doping has good properties. 304 stainless steels doped with titania characterised with XRD confirmed the TiO2 coating. Also, they showed that the broadening of the peaks was due to residual stresses in the substrate, present in the austenite phase of the substrate and a possible combination of fine grain and residual stresses in the TiO2 layer. SEM-EDS analyses confirm the roughness of the surface and elemental composition of stain steel doping with titania with 4.5 eV peak and 6.5eV peak. FTIR spectra also specify the Ti-O and Fe-O bonds in the prepared alloy. Topological modifications of 304 stainless steel surfaces caused by TiO2 plasma treatment can be quantified in terms of roughness by AFM analysis. It indicated that the rough surface was obtained due to the doping process. The biological application of the prepared alloy sample was tested using the immersion technique. The doped sample was subjected to a bioactivity test. The cytotoxicity results demonstrate a significant cytotoxic effect on CHO cells, which could be attributed to the high concentration of metal ions produced by the material's biocorrosion, which causes the culture medium's pH to change quickly, as indicated by a change in colour.